The second lome convention : an assessment with special reference to human rights - Smits, R.J.H. (Amsterdam : De Nederlandsche Bank N.V., 1980)
The present article deals with the main characteristics of Lome II against the background of the working of the First Convention so far and with a view to demands and expectations regarding the renegotiation
osc 29/10/2018
Loans
Keywords: International relations